2019
DOI: 10.1016/j.bbrep.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation cooperates with SNPs to modulate RAGE transcription and alter UC risk

Abstract: Single-nucleotide polymorphisms (SNPs) located in the promoter region of the receptor for advanced glycation end products (RAGE) gene have been linked to the activity of RAGE. However, contrary to our expectation, we previously detected no correlation between SNPs within the RAGE promoter and ulcerative colitis (UC) risk in a case-control study. Here, we investigated the methylation of the RAGE promoter and analyzed the collective contribution of methylation and SNPs to UC risk. We found that RAGE promoter hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“… 58 Besides, the variant of the RAGE rs1800625 SNP was suggested to be associated with the hypomethylation of the promoter region of RAGE and contribute to the ulcerative colitis risk. 59 Furthermore, after we analysed the TCGA database, we found that the RAGE mRNA level was significantly associated with prostate cancer tumorigenesis (Figure 1A ) and pathologic N1 stage development (Figure 1C ). The higher RAGE expression was also observed to be associated with lower overall survival rate in prostate cancer patients (Log Rank p = 0.025, Figure 1D ).…”
Section: Discussionmentioning
confidence: 94%
“… 58 Besides, the variant of the RAGE rs1800625 SNP was suggested to be associated with the hypomethylation of the promoter region of RAGE and contribute to the ulcerative colitis risk. 59 Furthermore, after we analysed the TCGA database, we found that the RAGE mRNA level was significantly associated with prostate cancer tumorigenesis (Figure 1A ) and pathologic N1 stage development (Figure 1C ). The higher RAGE expression was also observed to be associated with lower overall survival rate in prostate cancer patients (Log Rank p = 0.025, Figure 1D ).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, interaction of genetically associated genes and epigenetically associated genes in RA raised the possibility of cooperation of these two interacting systems to facilitate gene regulation in RA pathogenesis. It is possible that both methylation and genetic alterations were necessary for RA development and altered DNA methylation may be a second hit contributing to penetrance as demonstrated by complex multifactorial traits [27] and supported by past studies of autoimmune diseases [28].…”
Section: Discussionmentioning
confidence: 98%
“…Diabetes augments the expression of matrix metalloproteinase (MMP)-9 in the skin and its keratinocytes, and a high level of MMP-9 leads to impairments to skin wound healing, in which AGE-induced demethylation of MMP-9 promoter plays a key role ( Perrone et al, 2020 ). On the other hand, the methylation status in the RAGE promoter region exhibits key effects on multiple diseases ( Wang et al, 2019 ). Previous studies also revealed that RAGE promoter methylation status can function as an indicator for the diabetic retinal inflammation and RAGE gene promoters in DR patients, showing a lower methylation rate than that of healthy adults ( Kan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%